ANALISIS KANDUNGAN HIDROKUINON PADA PRODUK KRIM PEMUTIH WAJAH DENGAN MENGGUNAKAN METODE SPEKROFOTOMETRI UV-VIS - Dimas Sugianto; Izal Zahran; Jasril Jasril (JURNAL ETNOFARMASI, 2025)
Hydroquinone is an active ingredient that functions to control pigment production and reduce melanin formation in the skin. This is what causes a lot of hydroquinone to be used in whitening cream preparations. This research aims to determine the hydroquinone content in whitening creams available in the Belopa City Central market which do not have a BPOM registration number using the UV-Vis Spectrophotometry method. The samples in this study consisted of 10 samples with codes A, B, C, D, E, F, G, H, I, J. The results of the study showed that these 10 samples contained Hydroquinone with each brand sample level A = 17 %, B = 6.8%, C = 9.4%, D = 9%, E = 5.9%, F = 2.8%, G = 6.6%, H = 4.27%, I = 4.9%, and J = 0.08%. The highest hydroquinone content was obtained in sample A with a hydroquinone content of 17% and overall the hydroquinone content in each sample used exceeded the hydroquinone content limit set by BPOM, namely no more than 0%. Thus, these 10 samples must not be used as cosmetics, and must change the category to therapeutic products (drugs) or remove the Hydroquinone ingredient from the formula if they are still produced in the cosmetics category.